The effect of variation in concentration level (ATP) and its relationship to endurance status as a determinant of selection in some games and sports activities - Wali , A.D Majid Shandi; Daragh, A.M.D Maytham Kazem; Muhammad, Ameer Jassim (International Journal of Psychosocial Rehabilitation, 2020)
The problem of this study came in the lack of scientific research that dealt with the topics of the studied phenomenon, namely the energy index, which we find among the very important variables in the field of energy production for humans in general and athletes in particular, and the study aimed to identify the energy levels represented by (ATP) among the members of the research sample And to identify the relationship of the association of the level of concentration (ATP) and the trait of tolerance and according to the type of activity practiced as a determinant of the mathematical selection of the members of the research sample. The researchers concluded, the study showed a variation in the levels and concentrations of ATP among the subjects of the research sample and according to the type of activity, and the variance showed a correlation and according to the type of activity.